Monitoring Solid‐Phase Reactions in Self‐Assembled Monolayers by Surface‐Enhanced Raman Spectroscopy. Issue 33 (9th July 2021) - Scherrer, Dominik; Vogel, David; Drechsler, Ute; Olziersky, Antonis; Sparr, Christof; Mayor, Marcel; Lörtscher, Emanuel
Abstract: Nanopatterned surfaces enhance incident electromagnetic radiation and thereby enable the detection and characterization of self‐assembled monolayers (SAMs), for instance in surface‐enhanced Raman spectroscopy (SERS). Herein, Au nanohole arrays, developed and characterized as SERS substrates, are exemplarily used for monitoring a solid‐phase deprotection and a subsequent copper(I)‐catalyzed azide–alkyne cycloaddition "click" reaction, performed directly on the corresponding SAMs. The SERS substrate was found to be highly reliable in terms of signal reproducibility and chemical stability. Furthermore, the intermediates and the product of the solid‐phase synthesis were identified by SERS. The spectra of the immobilized compounds showed minor differences compared to spectra of the microcrystalline solids. With its uniform SERS signals and the high chemical stability, the platform paves the way for monitoring molecular manipulations in surface functionalization applications. Abstract : A highly reproducible, homogeneous plasmonic substrate was fabricated by electron‐beam lithography to detect the Raman fingerprints of molecular self‐assembled monolayers (SAMs) by surface‐enhanced Raman spectroscopy (SERS) at all points of the substrate with high uniformity. This substrate was employed for characterizing the intermediates and the product of a solid‐phase synthesis in a SAM by SERS.